Spotlight on spatial environmental policy spillovers: An econometric analysis of wastewater treatment in Mexican municipalities - Gunther Markwardt; Lutz Hecker; Frank Wätzold (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The objective of this paper is to analyze whether successful environmental policies spread across geographical space. We examine the existence of such environmental spatial policy spillovers using the example of wastewater treatment in Mexican municipalities. Untreated wastewater is a key pollution source in many developing and emerging countries, also in Mexico. However, wastewater treatment levels also differ greatly among the 2,456 Mexican municipalities. We apply spatial econometrics to explain differences in wastewater treatment. Our main finding is that a municipal administration is more likely to treat wastewater if neighboring municipalities do so. This insight seems of broader relevance to environmental policy-making. In developing and emerging countries, governments frequently lack capacities to solve environmental problems. Consequently, they may often rely on learning spillovers from nearby success cases. We recommend to implement environmental pilot projects which may then trigger domino effects.
Keywords: Q01; Q53; Q58; 330; spatial policy spillover; wastewater treatment; spatial econometrics; Mexico; social factors